The Role of Zakat in North Sumatra Province in Allevating the Poor - Muhammad Syafii; Weni Hawariyuni; Arif Rahman; Sukam Hayati Hakim (Universitas Medan Area, 2021)
Zakat distribution by BAZNAS is divided into utilization and distribution. The use of zakat for productive business is carried out when the basic needs of mustahik have been met. The Covid-19 pandemic caused the North Sumatra economy to experience growth of -2.37 percent in the 2nd quarter and -2.60 percent in the 3rd quarter. The sizeable economic inequality in North Sumatra is a challenge for BAZNAS in reducing the income gap between communities. The business income of productive zakat recipients before and after the pandemic is indicated to have differences. Asnaf in Medan City is quite representative portraits to see whether there are differences in income or otherwise. This study uses descriptive analysis and the Wilcoxon test model to examine the impact of productive assistance provided by BAZNAS on micro and small businesses. Researchers used net income before and after receiving productive assistance from North Sumatra BAZNAS. It is revealed stated that the provision of Zakat to asnaf could increase the income of asnaf, however during pandemic, the giving of zakat is decreasing as well as the income of asnaf also decreasing in North Sumatra Province